FRI0372 DMARD TREATMENT AND OPIOID USE IN EARLY SPONDYLOARTHRITIS IN FINLAND. (June 2019) - Muilu, Paula; Rantalaiho, Vappu; Kautiainen, Hannu; Virta, Lauri; Puolakka, Kari
Abstract : Background: Disease-modifying anti-rheumatic drugs (DMARDs) are introduced for the treatment of spondyloarthritis (SpA) after failure of non-steroidal anti-inflammatory drugs (NSAIDs). In Finland, try out with a conventional synthetic DMARD (csDMARD) is required before initiation of biologicals (bDMARD). The patients with DMARDs are eligible for a higher reimbursement for the cost of medication. Opioids are not recommended for arthritis pain. Objectives: To report the current DMARD and pain medication use among newly-onset SpA patients in Finland. Methods: From the nationwide reimbursement register maintained by the Social Insurance Institution of Finland we collected all incident adult patients with SpA (ICD-10 codes M45-46) between 2010-14 and divided them into two groups depending on whether bDMARDs were subsequently initiated (group B) or not (group A). Patients' drug purchases between 2009-15 were obtained from the Drug Purchase Register. Opioid use by these patients was evaluated one year before and after the index date (ID; the date when special reimbursement for antirheumatic drugs became effective), and compared to age, sex, and place of residence matched population controls. Intravenously administered bDMARDs (e.g. infliximab) were not included. Results: We identified 3577 SpA patients, 23% of which started a self-injected bDMARD during the observation period. More of the patients in group B needed pain medication, prednisolone, methotrexate, or other csDMARDs than sulphasalazine, which was more frequent in group A (table 1 ). Fifty-eight percent of the patients in group B started their bDMARD already within one year from ID (table 1 ). Overall, 29.8% of the SpA patients compared to 8.1% of the controls purchased opioids at least once during the year before ID. Patients' opioid purchases peaked during the last 3-month period before ID; risk ratios (RR) were 4.23 (95% confidence interval (CI) 3.63 to 4.84) and 6.23 (5.23 to 7.41) in patient groups A and B, respectively, compared to controls. SpA patients who had at least one opioid purchase during 12 months preceding the ID were 1.58 times more likely to start a bDMARD than those who did not purchase any opioids. Conclusion: Only one of four early SpA patients in Finland were initiated a self-injected bDMARD during 2010-15. The use of opioids before SpA diagnosis appears to be nearly four times more common among SpA patients compared to population controls, and early opioid purchases may act as a surrogate marker for further bDMARD initiation. Disclosure of Interests: Paula Muilu Grant/research support from: I have received a Congress trip from UCB Pharma and a Congress trip from MSD Finland outside the submitted work, Vappu Rantalaiho Grant/research support from: Dr. Rantalaiho has received a congress trip from Pfizer and a congress trip from Celegen outside the submitted work., Speakers bureau: Dr Rantalaiho reports a speaker's honorarium from Pfizer., Hannu Kautiainen: None declared, Lauri Virta: None declared, Kari Puolakka: None declared